Hypothesis in Language Learning Research - Mohammad Adnan Latief (TEFLIN, 2003)
Hypothesis is very often inevitable in research activities. Hypothesis is of at least three kinds, each of which should not be confused. A study trying to measure the relationship between variables can predict the finding based on theory or logical common sense. This prediction is called theoretical hypothesis. In testing hypothesis quantitatively, the theoretical hypothesis should be transformed into statistical hypothesis, which takes the form of Null hypothesis and its alternatives. It is the Null hypothesis that is to be tested to justify its rejection or otherwise its acceptance. In qualitative study, the result of first data analysis is called temporal empirical hypothesis that should be validated with more data. This cycle of rechecking the result with more data is done again and again until the hypothesis becomes the final conclusion.